Non-respiratory symptom dominance is associated with depression in patients with chronic obstructive pulmonary disease. (September 2022) - Hamakawa, Yoko; Sato, Susumu; Tanabe, Naoya; Rhee, Chin Kook; Jung, Ki-Suck; Yoo, Kwang Ha; Tanimura, Kazuya; Muro, Shigeo; Hirai, Toyohiro
Abstract: Introduction: Depression is a common and important comorbidity in patients with chronic obstructive pulmonary disease (COPD). Depressive status is associated with a high COPD assessment test (CAT) total score, but it is difficult to distinguish patients with depression from those with severe symptomatic COPD. We hypothesized that a non-respiratory symptom-dominant elevation in CAT score is associated with depression in patients with COPD. Methods: A total of 226 patients in the KYOTO cohort in Japan and 924 patients in the Korea COPD Subgroup Study (KOCOSS) cohort in the Republic of Korea were analyzed. Depression was diagnosed based on a PHQ-9 (patient health questionnaire-9) ≥5 in the KYOTO cohort and a BDI-II (Beck Depression Inventory-II) ≥17 in the KOCOSS cohort. Sums of respiratory symptoms (Q1-Q4; Q1234) and non-respiratory symptoms (Q5-Q8; Q5678) from CAT items were analyzed. Results: Fifty-three (23.5%) patients in the KYOTO cohort and 111 (11.2%) patients in the KOCOSS cohort were identified as having depression. Fifty-five patients (24.3%) in the KYOTO cohort and 249 patients (26.9%) in the KOCOSS cohort showed non-respiratory symptom dominance (Q1234 ≤ Q5678), and they had a significantly higher prevalence of depression than did patients with respiratory symptom dominance (Q1234 > Q5678). Multivariable logistic regression analysis showed that both the CAT total score and Q1234 ≤ Q5678 were significantly associated with depression in both cohorts. Moreover, even in symptomatic patients (CAT total score ≥10), these significant associations were preserved. Conclusion: Non-respiratory symptom dominance in CAT is a suspicious feature for depression in patients with COPD. Highlights: Depression is an important comorbidity in patients with COPD. Respiratory symptoms and non-respiratory symptoms in CAT items were analyzed. Non-respiratory symptom-dominant status in CAT is defined as Q1234 ≤ Q5678. Non-respiratory symptom-dominant status is associated with presence of depression.